Innovative Approaches in Bioinspired and Biomimetic Membrane Technologies: Bridging Nature and Engineering - Suvid Kumar Lingampally; Aishwarya Mantri; Shubham Jaju; Madhu Yasarapu (International Journal of Membranes, 2024)
Bioinspired and biomimetic membranes represent a ground breaking advancement in membrane technology, offering innovative solutions to critical global challenges in water purification, chemical separation, and energy conversion. These membranes leverage the exceptional transport properties of biological systems, particularly through the incorporation of aquaporin proteins, which facilitate rapid and selective water transport. This review synthesises recent developments in aquaporin-based membranes, highlighting their remarkable efficiency in desalination processes, where they serve as sustainable alternatives to traditional methods like reverse osmosis by significantly reducing energy consumption and enhancing water recovery rates. Furthermore, the versatility of these membranes extends to wastewater treatment, where they effectively remove contaminants while minimising fouling, thereby improving operational longevity and efficiency. In the food processing industry, aquaporin membranes are utilised for juice clarification and concentration, retaining essential flavours and nutrients without compromising product quality. The advancements in fabrication techniques—such as lipid bilayer assembly, thin film nanocomposites, and electrospinning—have paved the way for scalable production of high-performance membranes tailored for specific applications. However, challenges remain in terms of scalability, defect formation during production, and environmental stability that must be addressed through ongoing research and innovation. Future directions include the development of hybrid membrane systems that combine biomimetic designs with traditional materials, advanced characterisation techniques to optimise membrane structures, integration with nanotechnology to enhance performance, and a focus on sustainable material development to minimise environmental impact. As research continues to evolve in this dynamic field, biomimetic membranes hold significant promise for transforming water management practices and enhancing food processing methods globally, ultimately contributing to a more sustainable future.
Keywords: Bioinspired membranes; Food processing; aquaporin-based membranes; biomimetic membranes; desalination; sustainable membrane technology; wastewater treatment; water purification